Good Stories for Great Holidays : Arranged for Story-Telling and Reading Aloud and for the Children's Own Reading - Olcott, Frances Jenkins, 1872-1963 (Salt Lake City, UT : Project Gutenberg, 1995)
"Good Stories for Great Holidays" by Frances Jenkins Olcott is a collection of stories designed for storytelling and reading aloud, likely compiled during the early 20th century. This anthology features a variety of myths, legends, and historical tales associated with different holiday celebrations throughout the year, encouraging joy and discussion around these special occasions. The opening of the collection introduces the purpose behind the stories, emphasizing their suitability for arousing a festive spirit and teaching various moral lessons through engaging narratives. It discusses how the stories are adapted for storytelling, ensuring they are accessible for children's understanding. The introduction also highlights specific selections that will follow, which cover major holidays such as New Year's Day, Valentine's Day, and Christmas, offering a blend of themes from kindness and generosity to the excitement of festive traditions. (This is an automatically generated summary.)
Release date is 1995-11-01
Produced by Mike Lough, and David Widger
Keywords: Children's literature; Holidays; Short stories; Storytelling